2014
DOI: 10.1016/j.mjafi.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of skin-to-muscle and muscle-to-bone thickness on depth of needle penetration in adults at the deltoid intramuscular injection site

Abstract: Needles Subcutaneous fat a b s t r a c tBackground: The objectives of the study were to estimate the following in adults of Indian origin: a) Gender and side differences in the skin-to-muscle (SM) and muscle-to-bone thickness (MB) at the deltoid intramuscular injection site; b) Correlation of SM thickness with the BMI, age and gender; c) The prevalence of under and over-penetration assuming a standard needle length of 25 mm and following prescribed guidelines for IM injection. Methods: The SM, MB and skin-to-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Intramuscular injections require ‘penetration of the needle into the muscle layer by 5 mm or more to ensure that the injection would be into the muscle mass (Davidson & Rourke , Shankar et al . ). Our ultrasonographic study showed that the muscles of the children under 3 years of age in the ventrogluteal area had developed adequately.…”
Section: Discussionmentioning
confidence: 97%
“…Intramuscular injections require ‘penetration of the needle into the muscle layer by 5 mm or more to ensure that the injection would be into the muscle mass (Davidson & Rourke , Shankar et al . ). Our ultrasonographic study showed that the muscles of the children under 3 years of age in the ventrogluteal area had developed adequately.…”
Section: Discussionmentioning
confidence: 97%
“…Adequate penetration for IM injections is characterized by penetration of 5 mm or more into the muscle (Poland, Borrud, & Jacobson 1997;Shankar et al, 2014). Two different radiologists independently carried out the measurements of subcutaneous tissue and muscle thicknesses in the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm was chosen to have an average thickness of the skin and subcutaneous adipose fat tissues based on gender and BMI data extracted from the experiment conducted by Akkus ( 20 ) is considered in the algorithm. Estimation and relationship between the skin, fat, and muscle layers based on the fundamental parameters are given in Shankar et al ( 21 ), Bueno et al ( 22 ), and Mechelli ( 23 ). Similarly, the relationship between muscle and fat has been studied by Welch et al ( 24 ).…”
Section: Methodsmentioning
confidence: 99%